2020
DOI: 10.1055/s-0039-3400230
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Patellar Proximodistal Positioning with Limited Joint-Angle Sensitivity

Abstract: Objective Patellar luxation can be associated with abnormal proximodistal positioning of the patella. The current gold standard index (Insall–Salvati) for referencing this position is poorly suited to postoperative use, if the tibial tuberosity is moved surgically, but has the advantage of changing minimally with altered joint angles. The aim of this study was to identify an alternative index, which was simple to use, joint-angle insensitive and suitable for postoperative use. Study Design Candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 16 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…Thus, the ratio of the patellar ligament length to patellar length (PLL/PL) based on the Insall-Salvati index in humans was introduced as an index that is minimally affected by the stifle angle [6,[9][10][11]. Although some studies have introduced other indices to evaluate the proximodistal patellar position [2,12,13], these indices have not been used in clinical cases as often as the PLL/PL. Many canine studies have focused on the PLL/PL to discuss the proximodistal alignment between the patella and the femoral trochlea [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the ratio of the patellar ligament length to patellar length (PLL/PL) based on the Insall-Salvati index in humans was introduced as an index that is minimally affected by the stifle angle [6,[9][10][11]. Although some studies have introduced other indices to evaluate the proximodistal patellar position [2,12,13], these indices have not been used in clinical cases as often as the PLL/PL. Many canine studies have focused on the PLL/PL to discuss the proximodistal alignment between the patella and the femoral trochlea [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…11 To overcome these limitations, a recent study by Allberg and Miles proposed several easy-to-use osseous landmarks to be identified on radiographs in order to measure the position of the patella with a very limited impact of the SOA. 15 The same study suggests the fact that tibial osteotomies such as MMT could induce patellar luxation. 15 The objectives of this retrospective study were to verify in a large cohort of dogs the low sensitivity of the Allberg and Miles index (AM index) to SOA, evaluate the position of the patella in dogs pre-and post-MMT via that particular index and assess the incidence of patellar luxation post-MMT.…”
Section: Introductionmentioning
confidence: 87%
“…15 The same study suggests the fact that tibial osteotomies such as MMT could induce patellar luxation. 15 The objectives of this retrospective study were to verify in a large cohort of dogs the low sensitivity of the Allberg and Miles index (AM index) to SOA, evaluate the position of the patella in dogs pre-and post-MMT via that particular index and assess the incidence of patellar luxation post-MMT.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…2020). Additionally, concerns have been raised regarding whether the IS index is appropriate for use postoperatively when the TT has been moved (Allberg & Miles 2020). Due to this, a novel angular index, based on the caudal aspect of the femoral and tibial condyles and the apex of the patella has been proposed (Allberg & Miles 2020).…”
Section: Imagingmentioning
confidence: 99%